The economic contribution of sea angling from charter boats: A case study from the south coast of England. (September 2020) - Williams, Chris; Davies, William; Clark, Robert E.; Muench, Angela; Hyder, Kieran
Abstract: Marine Recreational Fisheries (MRF) provide important socio-economic contributions to coastal communities in the UK. Quantifying the contribution to coastal economies enables policy makers to plan for the sustainable development of these activities and consider trade-offs resulting from the implementation of regulations. Highlighting the importance of MRF enables their integration into fisheries management plans, tourism, and coastal infrastructure strategies, yet these effects are rarely quantified. In this study, the economic contribution of charter boat sea angling on coastal communities was assessed for four ports in Dorset on the South coast of England (Poole, Swanage, Weymouth and Portland). Poole and Weymouth have the largest charter fleets in the UK. Valuations from Poole and Swanage, as well as Weymouth and Portland were used alongside the numbers of boats in the fleet to estimate a cumulative economic impact to Dorset from charter boat activity of £2.4 million in gross output and providing about £3.6 million in estimated economic contribution and over £1.3 million of Gross Value Added (GVA). Future fisheries management should consider impacts and benefits when developing strategies for MRF, potentially distinguishing between different parts of the sector. This is particularly important for the charter fleet, as they are small businesses that rely on the value they generate to operate as businesses rather than being a pure recreational activity. Highlights: Marine Recreational Fisheries (MRF) contribute to coastal economies. The economic contribution is often not well understood or accounted for in policymaking. The economic contribution of charter boat angling was assessed for four ports on the South coast of England. Charter boats at the four ports supported £3.6 million of economic activity and £1.3 million of Gross Value Added (GVA). Future MRF management must consider the economic contribution of the charter boat fleet.